Microbiome composition of pneumonia in domestic pigs in Ukraine - Kokariev, A. V.; Kokariev, A.; Kokariev, Andrii; Kokarev, A. V.; Kokarev, A.; Kokarev, Andrey; Kokariev, Andrii V.; Кокарєв, Андрій Вікторович; Masjuk, D.; Masiuk, Dmytro; Masiuk, D. N.; Masiuk, D. M.; et al. (Дніпровський ДАЕУ, 2023)
Respiratory pathology in pigs is a widespread issue in global pig farming. The etiology of pneumonia varies and can significantly differ between regions. Periodically, new pathogens inducing respiratory diseases in pigs, including respiratory organs, are discovered worldwide. Therefore, the aim of our work was to determine the microbiome structure of pneumonia in domestic pigs in Ukraine. Fragments of lung tissue were collected for research from deceased pigs with signs of respiratory pathology. A total of 87 cases of pig pneumonia from 62 pig farms located in 20 different regions of Ukraine were investigated. Using the qPCR method, genes of 13 microorganisms were identified: PCV 2, PCV 3, SIV type A, SIV type D, PRRSV EU, A. pleuropneumoniae, A. suis, M. hyopneumoniae, M. hyorhinis, S. suis, P. multocida, B. bronchiseptica, and G. parasuis. It has been determined that the pneumonia microbiome in growing pigs is represented by a co-infection of 3-6 microorganisms, while in fattening pigs, it consists of 4-7 microorganisms. The maximum number of microorganisms in the pneumonia focus in both groups comprises 9 taxa. Some cases have been identified where none of the microorganisms were detected. The most prevalent microorganisms causing pig pneumonia are PCV2, G. parasuis, S. suis, M. hyorhinis, and P. multocida, whereas the least common are PCV3, PRRSV EU, and SIV type A. There is no evidence of SIV type D circulation among domestic pigs in Ukraine. There was found out the association for verified pneumonia events of growing pigs with dominant viruses PCV2 and PRRSV UA while an average concentration ranging from 108 to 109 genome equivalents per gram of lung tissue. In fattening pigs, PCV2 and A. pleuropneumoniae are most prevalent, with their average quantity varying from 107 to 109 genome equivalents per gram of lung tissue. PCV2 in most pneumonia cases appeared as a monoviral infection. Viral co-infections were identified involving PCV2, PRRSV UA, and PCV3. The least common respiratory virus is SIV type A, detected in only 2% of affected lungs. Bacterial pneumonia without viral involvement in growing pigs is significantly less common than in fattening pigs, but the bacterial spectrum is common for both groups, represented by M. hyorhinis, S. suis, and G. parasuis. Респіраторна патологія у свиней є широко розповсюдженою проблемою у продуктивному свинарстві всього світу. Етіологія пневмонії є різноманітною і може суттєво відрізнятись між регіонами. Час від часу у світі виявляють нові патогени, що індукують хвороби у свиней, у тому числі і респіраторних органів. Саме тому метою нашої роботи було визначити структуру мікробіому пневмонії у домашніх свиней України. Для проведення досліджень від загиблих свиней з ознаками респіраторної патології відбирали фрагменти легеневої тканини. Всього досліджено 87 випадків пневмонії свиней з 62 свинарських підприємств, що розміщені у 20 різних регіонах України. За допомогою методу qPCR виявляли гени 13 мікроорганізмів – PCV 2, PCV 3, SIV type A, SIV type D, PRRSV ЕU, A. pleuropneumoniae, A. suis, M. hyopneumoniae, M. нyorhinis, S. suis, P. multocida, B. bronchiseptica та G. parasuis. Встановлено, що мікробіом пневмонії у свиней групи дорощеня представлений коінфекцією з 3-6 мікроорганізмів, а у свиней на відгодівлі з 4-7 мікроорганізмів. Максимальна кількість мікроорганізмів у вогнищі пневмонії свиней обох груп складається з 9 таксонів. Виявлено випадки, у яких не виявлено жодного з мікроорганізмів. Виявлено, що найбільш поширеними мікроорганізмами за пневмонії у свиней є PCV2, G. parasuis, S. suis, M. нyorhinis і P. multocida, тоді як найменш поширеними є віруси PCV 3, PRRSV ЕU та SIV type А. Ознак циркуляції серед домашніх свиней України SIV type D не виявлено. З’ясовано, що домінуючими мікроорганізмами у вогнищі пневмонії свиней групи дорощеня є PCV 2 і PRRSV UA, середня концентрація яких коливалась у межах 108 -109 г.-е. у 1 грамі легеневої тканини. У свиней на відгодівлі найбільш поширеними є PCV 2 і A. pleuropneumoniae. Їх середня кількість коливаються у межах 107 -109 г.-е. у 1 грамі легеневої тканини. Отримані результати показали, що PCV 2 у більшості випадків пневмонії виявлявся у вигляді моновірусної інфекції. Коінфекцію вірусів виявлено за участі PCV 2, PRRSV UA і PCV 3. Найменш поширеним респіраторним вірусом є SIV type A, який виявлено лише у 2 % уражених легень. Бактеріальні пневмонії без участі вірусів у свиней на дорощені є значно менше поширеними ніж у свиней на відгодівлі, про те спектр бактерій є спільним для обох груп і представлений M. нyorhinis, S. suis і G. parasuis.
Структура мікробіому пневмонії у домашніх свиней в Україні
Кокарєв Андрій Вікторович https://orcid.org/0000-0002-5673-5984 Масюк Дмитро Миколайович https://orcid.org/0000-0002-2800-2580 Недзвецький Віктор Станіславович https://orcid.org/0000-0001-8975-6952 Гаращук Марина Іванівна https://orcid.org/0000-0003-1533-6490
Keywords: co-infection; коінфекція; pneumonia; запалення легень; swine circoviruses; цирковіруси свиней; bacteria; бактерії; microbiome; мікробіом